PENDAYAGUNAAN ZAKAT PRODUKTIF PADA KELOMPOK LAPAK BERKAH BINAAN IZI KOTA MAKASSAR - Trimulato Trimulato; Sudirman Sudirman; Ismawati Ismawati; Supriadi Supriadi; Samsul Samsul; Ismail Halim (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
Zakat is an obligation for every Muslim because zakat is one of the pillars of Islam. The benefits of tithing include two dimensions, namely the spiritual dimension and the social dimension. A spiritual dimension is a form of obedience in carrying out religious orders, while the social dimension is the implementation of a caring attitude among fellow Muslims. Zakat is very useful to ease the economic burden of the poor. The distribution of zakat is not only to meet the needs of daily life but can also be distributed in the form of working capital assistance so that zakat funds can be productive. Management of zakat funds will be productive if it can be managed professionally. Therefore, to realize this goal, we, from the Department of Sharia banking, Faculty of Economics and Islamic Business, State Islamic University, Makassar, are moved to carry out community service activities that are packaged in the form of empowerment activities and business management assistance. The method used in community service activities with the theme of Empowerment of Productive Zakat as an effort to strengthen the economy of the community who are members of the Blessings group under the guidance of the Indonesian Zakat Initiative in Makassar. Stages of activity, first conducted observations to obtain initial information related to the condition of the target group. The next stage is to draw up a plan for empowerment and mentoring activities. Next, conduct education through lecture methods, discussions, and consultations related to business management. Speakers describe business management and market-building strategies. The next stage is to assist by conducting regular consultation visits every month. The results of these activities can help provide solutions to various problems in business management, both in terms of financial management and marketing aspects.